Participaç\~ao social e as conferências nacionais de políticas públicas: Reflex\~oes sobre os avanços e desafios no período de 2003-2006 - Enid Rocha Andrade da Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– The study evaluates the performance the process of the social participation around of the national conventions of the public policies, that they had taken place in 2003 to 2006, putting in relief the improvement and the challenge.
Keywords: D70; H83; Z10; Z13; 330